The Regulatory Framework, Practical Challenges, and Solution Pathways for Cross-Border Data Flow - Wan, YaJun (International Theory and Practice in Humanities and Social Sciences, 2025)
To date, the global community has yet to establish a unified and widely acknowledged framework for data flow standards. Given the role of cross-border data flow in advancing globalization, this study examines the collaborative governance approach to cross-border data flow in China, aiming to offer insights that can enhance the efficiency of such governance in the country. By comparing and analyzing the regulatory models employed by the United States, the European Union, and China in the formulation of cross-border data flow regulations, this paper suggests practical revisions to the rules of each jurisdiction. Furthermore, it outlines a pathway to alleviate the challenges associated with the collaborative governance of cross-border data flow in China, by addressing the existing dilemmas. The paper recommends several concrete measures to ensure the mutual protection of sovereignty and data security through enhanced multilateral agreements, to develop comprehensive cross-border data regulations via the establishment of pertinent international legal frameworks, to facilitate seamless cross-border data flow through the widespread adoption of international data laws, and to take into account the broader implications of technological advancements in resolving cross-border data flow issues. The ultimate goal is to foster the long-term, sustainable, and healthy development of China’s collaborative governance of cross-border data flow.